Endoperoxide antimalarials: development, structural diversity and pharmacodynamic aspects with reference to 1,2,4-trioxane-based structural scaffold - Rudrapal M; Chetia D (Dove Medical Press, 2016)
Mithun Rudrapal, Dipak Chetia Department of Pharmaceutical Sciences, Dibrugarh University, Dibrugarh, India Abstract: Malaria disease continues to be a major health problem worldwide due to the emergence of multidrug-resistant strains of Plasmodium falciparum. In recent days, artemisinin (ART)-based drugs and combination therapies remain the drugs of choice for resistant P. falciparum malaria. However, resistance to ART-based drugs has begun to appear in some parts of the world. Endoperoxide compounds (natural/semisynthetic/synthetic) representing a huge number of antimalarial agents possess a wide structural diversity with a desired antimalarial effectiveness against resistant P. falciparum malaria. The 1,2,4-trioxane ring system lacking the lactone ring that constitutes the most important endoperoxide structural scaffold is believed to be the key pharmacophoric moiety and is primarily responsible for the pharmacodynamic potential of endoperoxide-based antimalarials. Due to this reason, research into endoperoxide, particularly 1,2,4-trioxane-, 1,2,4-trioxolane- and 1,2,4,5-teraoxane-based scaffolds, has gained significant interest in recent years for developing antimalarial drugs against resistant malaria. In this paper, a comprehensive effort has been made to review the development of endoperoxide antimalarials from traditional antimalarial leads (natural/semisynthetic) and structural diversity of endoperoxide molecules derived from 1,2,4-trioxane-, 1,2,4-trioxolane- and 1,2,4,5-teraoxane-based structural scaffolds, including their chimeric (hybrid) molecules, which are newer and potent antimalarial agents. Keywords: endoperoxide, structural diversity, 1,2,4-trioxane, pharmacophore, pharmacodynamic, antimalarial